"Is it me or should my friends take the credit?" The role of social networks and social identity in recovery from addiction. Issue 1 (January 2017) - Bathish, Ramez; Best, David; Savic, Michael; Beckwith, Melinda; Mackenzie, Jock; Lubman, Dan I.
Abstract: This study explored the role of social network and social identity factors in recovery from addiction. The sample consisted of 537 individuals who completed a survey about their experiences of recovery. Results indicated that the transition from addiction to recovery was characterized by an increase in social connectedness and changes in social network composition coupled with the emergence of a "recovery" identity. These factors accounted for 14% of the variance in quality of life when controlling for known predictors, accounting for a greater proportion of variance than substance use variables. Results suggest that recovery from addiction can be understood as a socially mediated transition characterized by social network and social identity change, which drive broader improvements in quality of life.